Buying for good: Altruism, ethical consumerism and social policy. (6th May 2021) - Le Grand, Julian; Roberts, Jonathan; Chandra, Gauri
Abstract: The extent of altruistic behaviour and its relationship to the market has been a major interest of social policy analysts since the pioneering work of Richard Titmuss. Here we report on empirical research into such behaviour in consumer markets where self‐interest might be expected to dominate but whose participants are increasingly demonstrating more ethical concerns. We discuss three factors that have been hypothesized to affect the extent and depth of altruistic behaviour by individuals in such markets: the degree of personal sacrifice involved in the purchase, the reputation of individuals with their family and friends and individuals' sense of self‐identity. Using an online survey method, we measure consumers' motivations for real purchases in two different ethical consumerism settings: (RED) and Fairtrade. We find evidence to support all three hypotheses and conclude with some of the implications for social policy.